Multiple Sclerosis in Malaysia: Demographics, Clinical Features, and Neuroimaging Characteristics. (26th December 2013) - Viswanathan, S.; Rose, N.; Masita, A.; Dhaliwal, J. S.; Puvanarajah, S. D.; Rafia, M. H.; Muda, S.
Abstract : Background . Multiple sclerosis (MS) is an uncommon disease in multiracial Malaysia. Diagnosing patients with idiopathic inflammatory demyelinating diseases has been greatly aided by the evolution in diagnostic criterion, the identification of new biomarkers, and improved accessibility to neuroimaging in the country. Objectives . To investigate the spectrum of multiple sclerosis in Malaysia. Methods . Retrospective analysis with longitudinal follow-up of patients referred to a single tertiary medical center with neurology services in Malaysia. Results . Out of 245 patients with idiopathic inflammatory demyelinating disease, 104 patients had multiple sclerosis. Female to male ratio was 5 : 1. Mean age at onset was 28.6 ± 9.9 years. The Malays were the predominant racial group affected followed by the Chinese, Indians, and other indigenous groups. Subgroup analysis revealed more Chinese having neuromyelitis optica and its spectrum disorders rather than multiple sclerosis. Positive family history was reported in 5%. Optic neuritis and myelitis were the commonest presentations at onset of disease, and relapsing remitting course was the commonest disease pattern observed. Oligoclonal band positivity was 57.6%. At disease onset, 61.5% and 66.4% fulfilled the 2005 and 2010 McDonald's criteria for dissemination in space. Mean cord lesion length was 1.86 ± 1.65 vertebral segments in the relapsing remitting group as opposed to 6.25 ± 5.18 vertebral segments in patients with neuromyelitis optica and its spectrum disorders. Conclusion . The spectrum of multiple sclerosis in Malaysia has changed over the years. Further advancement in diagnostic criteria will no doubt continue to contribute to the evolution of this disease here.